Strategi Implementasi Kurikulum Merdeka Untuk Anak Berkebutuhan Khusus Di Sekolah Inklusi School Of Universe - Fitrah Febri Salam; Nur Amalia Zahra; Siti Mariyatul Koimah (CV. Kurnia Grup, 2024)
This study focuses on the implementation of the Kurikulum Merdeka in inclusive education for children with special needs at the School of Universe, a school that adopts an inclusive education system. The identified problem is how the curriculum can be adapted to support the diverse learning abilities of students, particularly those with special needs. The aim of this study is to analyze the strategies and approaches used in teaching, as well as the role of teachers in supporting the learning process of students with special needs. The research method employed is qualitative with a case study approach, where data were collected through in-depth interviews, observations, and analysis of relevant documents. The results show that curriculum adjustments, such as the use of flexible teaching methods and the integration of technology, can improve motivation, engagement, and learning outcomes for students with special needs. Furthermore, the support provided by teachers through individualized teaching approaches plays a significant role in creating an inclusive learning environment. The conclusion of this study highlights the importance of flexibility in curriculum implementation and the need for teacher training focused on developing skills to manage diverse student abilities in inclusive schools. This research makes an important contribution to the development of inclusive education in Indonesia.